Implementation of behaviorism theory in the formation of positive behavior at muhammadiyah 1 middle school kartasura - Hafidz Hafidz; Faizatul Maslahah; Nurul Latifatul Inayati; Muhammad Chafidz Ali Wafa (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2023)
This This study aims to: (1) find out the implementation of behaviorism theory in cultivating positive behavior at SMP Muhammadiyah 1 Kartasura.  (2) discover the inhibiting factors and supporting factors for implementing the theory of behaviorism in cultivating positive behavior at SMP Muhammadiyah 1 Kartasura.  The method used is field research.  With a phenomenological approach and using observation data collection techniques, documentation and interviews. Data analysis carried out namely data reduction, data presentation, and data verification or conclusions.  The findings show that: the application of the theory of behaviorism at Muhammadiyah 1 Kartasura Middle School is in the form of a stimulus given starting from habituation in the morning, application of smiles, greetings and salutation, as well as discipline exemplified by the teacher.  The theory of behaviorism is a theory that emphasizes changes in the behavior of an individual after getting a stimulus.  The use of behaviorism theory is quite efficient in cultivating positive behavior in students at SMP Muhammadiyah 1 Kartasura.  This can be seen from the number of students who show a positive response in line with expectations.  Habituation that is done before learning in class begins is a form of stimulus that is carried out by the teacher.  With the stimuli that have been given to students, many students experience changes in behavior in a positive direction.  In addition to habituation at school, parental attention is also very influential on student behavior.  Student psychology is one of the important things that influence the learning process, so special attention is needed in providing stimulus.